Feasibility study on saturated water cooled solid oxide fuel cell stack. (1st December 2020) - Promsen, Mungmuang; Komatsu, Yosuke; Sciazko, Anna; Kaneko, Shozo; Shikazono, Naoki
Graphical abstract: Highlights: Concept of cooling SOFC stack with phase change heat transfer of saturated water. SOFC temperature distribution is considerably improved. Air flow rate and parasitic power consumption can be greatly reduced. Abstract: In the present study, a novel concept of cooling solid oxide fuel cell (SOFC) stacks with phase change heat transfer of saturated water is proposed in order to provide an additional means to control the temperature distribution of SOFC stacks with small parasitic energy consumption. Three-dimensional computational fluid dynamics modeling with an electrochemistry solver is used to simulate the SOFC operations. By comparing the proposed water-cooled stack with the conventional air-cooled stack, it is found that water cooling significantly improves the temperature distribution inside the stack, leading to better electrochemical performance. The temperature difference of the tubular SOFC can be reduced from 295 K in the air-cooled stack to 62 K in the water-cooled stack with the same operating conditions. In the planar SOFC, it can be reduced from 185 K to 26 K. It is also shown that water cooling can greatly reduce the air flow rate in the stack without much affecting the thermal condition. Using water cooling, air utilization can be as high as 80%, leading to the reduction of parasitic air blowing power.